Study on the Stress–Strain Relationships and Deterioration Modes of HTPB Propellant with Prefabricated Cracks - Bo Gao; Zhuo Li (Advances in Polymer Technology)
Penetrating cracks with different crack angles were prefabricated in viscoelastic hydroxyl-terminated polybutadiene propellant specimens. Microphotography was performed while tensile tests were conducted on a universal testing machine at tensile rates of 2 mm/min, 10 mm/min, and 500 mm/min. Specimen measurements were obtained by digital image correlation (DIC). The strain fields on the surfaces and around the cracks were studied, and the crack propagation trends for precracked specimens with angles of 0°, 45°, and 75° with respect to the horizontal plane were investigated. Stress–strain curves, tensile microscopic images (50x magnification), and fracture microscopic images (100x magnification) were obtained for different prefabricated crack angles and different stretching rates. It was observed that under low-rate stretching, the propellant crack growth exhibited three stages: a linear stage, a yield stage, and a failure stage. However, the crack propagation in the propellant under high-speed stretching had no yield stage. When there were no prefabricated cracks, a greater tensile rate led to a greater ultimate strain. The maximum strains at the crack tips measured by DIC decreased from group C1 to groups C2, C3, and S. The specimens corresponding to different crack inclination angles are pulled off. It was seen that the closer a crack was to positive breaking, the straighter was the edge notch of the specimen.